Experimental Study on a Small-scale R245fa Organic Rankine Cycle System for Low-grade Thermal Energy Recovery. (May 2017) - Li, L.; Ge, Y.T.; Tassou, S.A.
Abstract: This work conducted an experimental investigation of a small-scale organic Rankine cycle (ORC) system at designed operating and control conditions for low-grade thermal energy recovery application. In the ORC system, R245fa was selected as working fluid while a turboexpander (turbine) with a high speed and permanent magnet synchronous electricity generator was installed to produce electric power and two-plate type heat exchangers were designed as an evaporator and condenser. The effects of condenser cooling water temperatures and R245fa superheat at the turbine inlet on the system performance were measured and analyzed. Practically, to ensure safe operation of the ORC expander, the R245fa superheat at the expander inlet is controlled to remain constant. The experimental results showed that at constant heat source parameters (temperature and flow rate), the turboexpander power output and cycle efficiency increased with lower cooling water temperatures. Under the specified test condition ranges, the maximum turboexpander power generation could achieve 5.405 kW when the cooling water temperature and the pressure ratio were set at 23.0 °C and 7.3 respectively. On the other hand, at certain cooling water temperatures, the superheat at the expander inlet exerted a negative impact on the turboexpander and system performances when the evaporating pressure was kept constant. Ultimately, the superheat was found to be an important control parameter to ensure efficient and safe system operation.